A space management model for optimizing spatial performance of mosques in Kuala Lumpur, Malaysia - Asif, Naysayer (2018)
Government expects the population in Greater Kuala Lumpur will grow from six million to 10 million by 2020 under the Economic Transformation Programme (ETP). The development of Malaysia is now guided by the national agenda and Vision 2020 that envisions Malaysia as a fully developed country economically, socially, politically and spiritually by the year 2020. Religious facility requirement for Vision 2020 states 309 new mosques and surau have to be established to fulfill the need of the growing population. While the land constraints remain for the city of Kuala Lumpur, the need of the growing population cannot be overlooked. This necessitates developing an innovative tool which can provide a layout for maximizing the space use within the limited boundary. This research studies the current space use patterns and formulates design framework for the mosque as a community center in the urban fabric of Kuala Lumpur. The method being used here is a combination of qualitative and quantitative approach. The sample consisted of 28 mosques in Kuala Lumpur distributed within 6 zones. The findings show that on an average only 38.48 % of the time the mosques are utilized with activities while only 5.76 % of its available spaces are occupied during the activities. As a result, the average space utilization rate of the mosques of Kuala Lumpur turns out to be extremely low, only 2.22 %, causing wastage of valuable resources and financial burden. Recommendations include proposal for increased activities and introducing flexible usage of the spaces as well as distribution of the functional spaces based on the requirement of the population. This study will give a huge impact on the development of the Muslim community in particular and the public in general through a model for space management. Further study may include in-depth analysis of spatial usage pattern of individual mosque for a longer period of time as well as include more typologies, i.e., surau to be analyzed.